THE CORRELATION BETWEEN VISUAL LEARNING METHODS AND STUDENTS’ READING COMPREHENSION IN EFL VOCATIONAL SCHOOL - Widodo Nur Ilham; Hanif Nurcholish Adiantika; Dila Charisma (National Conference on Language, Education, and Technology Proceeding, 2023)
This research investigates the correlation between visual learning methods and students’ reading comprehension, also examines the effectiveness of visual learning method in one vocational school in Brebes. Learning reading for multimedia students is still at the average value. In this study, researcher used experimental research with a quantitative approach. Researcher want to know the effectiveness of using visual learning methods in teaching English on students' understanding through experimental research. Impact is assessed by giving special treatment. There are many primary data collection methods. Main methods such as Questionnaires, Interviews. The participants in this study are class XI students. This study employs quota sampling to select participants for the interview and test portion The first finding is Visual Learning There is strong correlation between visual learning and EFL (English a Foreign Language) classroom. They learn by watching demonstration, reading text with illustration, and using visual aids. The second finding is effectively visual learning in EFL classroom Visual learning is highly effective way to learn reading in a multimedia program. Visual learners are able to process information more easily when it is presented in a visual format, such as through chart, graph, diagram, or video. Therefore the results of testing the hypothesis indicate that there is a significant influence between visual learning methods on learning English has an effect on learning English. Rresults obtained are 6.64> 2.060 meaning tcount greater than ttable. So from these results we can know if there is a significant influence of the use of visual learning methods on learning English.